Mengurai Kepatuhan Pajak UMKM: Dimensi Informasi dan Efektivitas Pemungutan - Farida, Arif; Wijayanti, Handayani Tri; Sriyanto, Sriyanto (STIE Atma Bhakti, 2025)
This study aims to analyze the influence of tax socialization, tax knowledge, and the effectiveness of the tax collection system on tax compliance among Micro, Small, and Medium Enterprises (MSMEs). These three independent variables are examined within the framework of the Theory of Reasoned Action (TRA) to understand tax compliance behavior from the perspectives of attitude and subjective norms. The research employs a quantitative approach using a survey method involving 100 MSME respondents in Surakarta City who possess a Taxpayer Identification Number (NPWP). Data analysis was conducted using multiple linear regression, preceded by validity, reliability, and classical assumption tests. The results indicate that all three independent variables significantly influence tax compliance, both simultaneously and partially. Tax socialization contributes to building taxpayer awareness and social norms, while tax knowledge fosters a positive attitude toward compliance. The effectiveness of the tax collection system, particularly those based on technology, simplifies administrative processes and enhances taxpayer trust. Therefore, improving MSME tax compliance can be achieved through continuous education, enhanced tax literacy, and the optimization of a responsive and integrated tax system.